Pregled razvoja metod za določanje vitamina D v krvi - Mlekuš, Katarina (Farmacevtski vestnik, 2022)
Vitamin D is a fat-soluble vitamin that plays an important role in the human body and enables the proper functioning of several organ systems. Interest in vitamin D grew especially in the first decade of the 21st century when its role in the pathogenesis of various diseases was first mentioned. At that time, a demand for laboratory measurements of 25-hydroxyvitamin D that is used to assess the vitamin D body stores rose sharply, so most clinical laboratories had to abandon laborious manual methods and had to introduce various automated techniques. Due to different methodologies, the inter-laboratory variability of measurements increased, which led to inconsistent conclusions in studies and meta-analyses in this research field. The Vitamin D Standardization Program has been established in recent years. The main goal is to reduce the variability of measurements and to promote comparisons of individual laboratories’ measurements to the reference method.
Keywords: 25-hidroksivitamin D; 25-hydroxyvitamin D; immunological assay; imunološki testi; masna spektrometrija; mass spectrometry